Anonymous
Anonymous asked in Science & MathematicsMathematics · 5 months ago

√3+√27 How to do Step please Thx?

Update:

Simplify it

15 Answers

Relevance
  • 5 months ago

    = 4*sqrt(3) =~ 6.928

  • 5 months ago

    √3 + √27

    = √3 + √(9 * 3)

    = 1*√3 + 3*√3

    = 4√3

  • Ian H
    Lv 7
    5 months ago

    √(27) = √(9)*√(3) = 3√(3), so,

    √(27) +√(3) = 4√(3)

  • 5 months ago

    = √3 + √27

    = √3 + √(9 * 3)

    = √3 + (√9 * √3)

    = √3 + (√3² * √3)

    = √3 + (3 * √3)

    = √3 + 3√3

    = 4√3

  • What do you think of the answers? You can sign in to give your opinion on the answer.
  • 5 months ago

    √3 + √27

    Simplify the square root of 27, knowing that you can factor a 9 out of it which is a perfect square to get:

    √3 + √(9 * 3)

    √3 + 3√3

    Now you can combine like terms to get:

    4√3

  • 5 months ago

    √3 + √27

    = √3 + 3√3

    = 4√3

  • 5 months ago

    First you find the square root of each, THEN you add them.

  • David
    Lv 7
    5 months ago

    It is the same as (1 times square root of 3 )+ (3 times the square root of 3) = 4 times square root of 3

    The simplest way is to use your calculator.

  • TomV
    Lv 7
    5 months ago

    How to do what? What do you want done with the expression?

    The expression can be written in a simpler form if you recognize that √3 is a factor of both terms.

    √3 + √(3*9)

    = √3 + 3√3

    = 4√3

    • TomV
      Lv 7
      4 months agoReport

      Because √3 + 3√3 = (1)√3 + (3)√3 = (1+3)√3 = 4√3

  • J
    Lv 7
    5 months ago

    use √27 = √(9 * 3) = 3√3

    • J
      Lv 7
      5 months agoReport

      I was hoping the OP knew that x + 3x = 4x and could instantiate with x= √3

Still have questions? Get answers by asking now.